Bilateral Symmetry and Perceptual Reversals. (January 2014) - Deręgowski, Jan B
Imposition of patterns varying in symmetry about the observer's median plane on a reversible figure affects duration for which each of the fluctuating percepts is experienced. Symmetry of the imposed patterns is associated with lesser difference between the two durations. This effect is particularly pronounced when the patterns are enantiomorphic and therefore jointly form a symmetrical pattern, but is also present when the patterns are symmetrical but unrelated.